Pareto Improving Climate Policies: Distributing the Benefits across Generations and Regions - Michael Hoel; Sverre A.C. Kittelsen; Snorre Kverndokk (Center for Economic Studies and ifo Institute (CESifo), 2015)
Most studies show that the present generation has to take the burden and reduce consumption to mitigate future climate change. However, significant climate change is due to a market failure, and corrections of market failures give possibilities of Pareto improvements. In this paper, we study the implication of Pareto improving climate policies. We use the representative consumer model RICE-10, which is a global model with different regions, to see how the benefits can be distributed across and within generations. The model shows that while the social optimum by definition is on the Pareto efficiency frontier, it is not necessary on the Pareto improving frontier, and that different combinations of present and future consumption along the Pareto improving frontier would give different combinations of capital investments and emissions. We find that all Pareto improving policies have higher total emissions than the social optimum when transfers are allowed. Without the possibility of transfers, total emissions may be lower than under the social optimum. Moreover, in this case carbon taxes differ substantially between regions for all Pareto improving policies.
Keywords: C63; D63; D99; H23; Q54; 330; Pareto improvements; climate agreements; intergenerational distribution; intragenerational distribution